Vaginal cleansing soap causes pathological vaginal discharge: a case study - Widyatama, Haryo Ganeca; Kusumaningrum, Dietha; Rajagukguk, James Bernardo; Safitri, Mesty Mela; Asri, Inaya Larang (Jurnal Ilmiah Kesehatan Sandi Husada, 2024)
Introduction: Vaginal discharge or another name is flour albus or leukorrhea, which occurs in women who are teenagers or of childbearing age. 75% of women will experience vaginal discharge at least once in their lives. Abnormal vaginal discharge is caused by infection from various microorganisms. In Indonesia alone, 90% of women are at risk of experiencing pathological vaginal discharge due to the tropical climate. Women often do vaginal cleaning or vaginal douching. Usually, this activity uses vaginal cleansing fluid. Objective: This study aims to dig deeper into the relationship between the use of vaginal cleansing soaps and pathological vaginal discharge in women, hoping to provide better insight into the effects of using these products and provide appropriate health recommendations. Method: The research design uses a descriptive case study method which aims to describe the relationship between two things experienced by the patient, namely vaginal discharge and the habit of cleaning the vagina with vaginal cleansing soap. Results: A 30-year-old woman came to the clinic with complaints of vaginal discharge coming out of her vagina. The vaginal discharge also feels thick, smells fishy, ​​and feels very itchy in the vaginal area. On physical examination, mucopurulent vaginal discharge with a fishy odor was found. The labia majora looks swollen and red. By using a speculum, the cervix appears reddish. No abrasions or blood spots were found on the cervical neck. Conclusion: There is a relationship between the use of vaginal cleansing soap and the emergence of pathological vaginal discharge. Changes in the acidity of the vagina influence the emergence of pathological flora. There is a need to increase Knowledge of how to maintain vaginal cleanliness, not just using vaginal cleansing fluids. With this study, it is further proven that the use of vaginal cleansing soap can cause pathological vaginal discharge. It is necessary to have good education for women with pathological vaginal discharge so that there is no recurrence of similar cases. In the case study above, it is essential to carry out additional examinations to find out the cause of the vaginal discharge, whether it is fungus, bacteria, or protozoa so that it can speed up the healing of the patient. With this research, it is also hoped that it can be an example of health care about pathological vaginal discharge and increase women's Knowledge of what kind of good vaginal cleaning behavior.